Materializing Digital Futures: Touch, Movement, Sound and Vision - Cinque, Toija and Beth Vincent, Jordan (Bloomsbury Academic & Professional, 2022)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Figures -- Contributors -- Acknowledgements -- Introduction -- SECTION one Socio-aesthetics of sound and sight -- 1 Virtual reality, the chiasm and the doubled body (Angela Ndalianis) -- 2 Sensing Sims: Atmospheres, aesthetics and the cyborg player (Merlin Seller) -- 3 Embodied audiovisual experience: The role of sound in contemporary screen and digital media (Darrin Verhagen and Ben Byrne) -- 4 Volumetric Black: Post-cinematic Blackness (Triton Mobley) -- SECTION two Meaning-making in the data-driven era -- 5 Quantified me: Curatorial lives and the pixelated spectre of self (Toija Cinque) -- 6 Virtual reality and kinaesthetic connection: Qualities of 'being there' (Kim Vincs) -- 7 Feminist memes: Digital communities, identity performance and resistance from the shadows (Shana MacDonald and Brianna I. W -- 8 The infinite portrait: A case of post-human authorship (Andrew McIntyre) -- SECTION three Touch, body, metal, screen -- 9 First encounters with robots through embodied observation, imagined narrative and choreography (Amy LaViers) -- 10 Physical digitality: Making reality visible through multimodal digital affordances for human perception (Luke Heemsbergen, -- 11 A true feel: Re-embodying the touch sense in the digital fashion experience ( Michela Ornati) -- 12 What robots learn from performative relationships and interactive performance (Steph Hutchison and John McCormick) -- SECTION four Digital futures -- 13 Smart home: Smart devices and the everyday experiences of the home (Xi Cui) -- 14 Affect and the digitalization of war (John MacWillie) -- 15 Automation is a myth (Luke Munn) -- 16 A triadic typology of material mediation: Ontology, intentionality and vitalism (Renata Lemos Morais) -- Index.
https://katalog.adlr.link/Record/0-180016095X